Solutions for the conservation and restoration of cement-based materials in XX Century architectural heritage - Pizzigatti, Cesare <1983> (Alma Mater Studiorum - Università di Bologna, 2022)
Among the most representative materials of XX Century architectural heritage, this dissertation focuses on the cement-based ones, investigating some different fields where they were exploited. Primarily, concerning the surface preservation of cement-based materials used with aesthetic intent, new self-cleaning treatments based on titania nanoparticles embedded in inorganic matrices were tested. In order to consider the role of porosity, the treatments were applied to different kinds of materials (cement-based mortar, marble and concrete) and several analyses were conducted to investigate the morphology of the coatings, their photocatalytic effectiveness, their durability and the interaction between the coating and the substrate material. The outcomes showed that several parameters influence the treatment’s performances, in particular, the presence and nature of the matrix, the concentration and dispersion of nanoparticles and, in some cases, the amount of substrate material which interacts with the coatings. Secondly, this dissertation deals with the historic “Terranova” render, a colored dry-mix mortar largely widespread in Europe in the first half of XX Century, whose formulation is still basically unknown. Some original samples of supposedly Terranova renders were subjected to several characterization analyses and the results were compared to those of the original “Terranova” render of the Engineering Faculty in Bologna. Despite the recurrence of some features, defining a common formulation seemed to be challenging. Finally, the repair and conservation of structural reinforced concrete in heritage buildings were investigated, adopting the former “Casa del Fascio” in Predappio (FC, Italy) as case study. Three different materials and solutions were tested on a slab of the building, making its repair only from the intrados. Then several analyses were conducted both on site and in laboratory. Aside from the specific features characterizing every product, the results highlighted that the application method played ...